"Oriental Component" and Socio-Cultural Environment in Kazan in the Early 1920s - Nivina, Olga Yuryevna; Martynov, Dmitry Evgenyevich; Martynova, Yulia Aleksandrovna; Valeev, Ramil Mirgasimovich (Journal of History Culture and Art Research, 2017)
This research investigates some aspects of a sociocultural situation in Kazan in the first years of the Soviet power. The research is conducted in the context of development of musical culture and education. The main method is biographic, and the institutional biography with the emphasis on the identity of orientalists, especially Nikolay Katanov is considered (1862-1922). The major conclusion is that all major actions of the Soviet power in the field of music education were prepared by processes in orientalist community, since the end of the 19th century. It is shown that representatives of suburbs of the Russian Empire gave help to capital scientists in carrying out researches and began to have significant effect on representations of the teachers. This influence readily admitted, as well as full equality. An example is the scientific and cultural environment of Kazan in which interest of the authorities, served musical and scientific community to culture of the people of the East as an incentive to creation in Kazan of the first special musical facility - East conservatory in 1921. Materials of the research are of interest as to researchers of the sociocultural environment in Russia in the 1920th years, and to historians of culture and music education.